Da’wah Strategy in the Digital Era - Alwi, Engku Ahmad Zaki bin Engku (Proceedings of International Conference on Da'wa and Communication, 2024)
Da’wah in the digital era is currently the most necessity and the latest trend because the global community, especially the younger generation, is very inclined to seek religious knowledge through new media. Social media is one of the media that is in great demand today because it has flexible nature and can be easily accessed through various social media platforms. This writing aims to analyze opportunities and challenges, as well as a social media strategy model as an effective digital da’wah media. The research method used is library research to analyze various library sources with in-depth analysis to analyze the formulation of the research problem. The results of the research show that social media is an effective digital da’wah media because it can transform religious knowledge to the audience; can be collaborated with other media; alternative media to disseminate audio content for both individuals and congregations; can be accessed safely and comfortably. The strategies used by preachers to manage digital da’wah through social media include recognizing the characteristics of the da’wah object, composing an attractive da’wah message, using appropriate da’wah methods, and using media according to the target.